PERBANDINGAN POLA ASUH DAN STATUS GIZI ANAK USIA 7-59 BULAN ANTARA ORANG TUA TUNGGAL DAN BUKAN ORANG TUA TUNGGAL (Studi di Kecamatan Pati Kabupaten Pati Provinsi Jawa Tengah Tahun 2019) - Hanna Ela Monnica; Laksmi Widajanti; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The problem of instability in the family is increasing, one of which is a single parent, especially those carried by the mother. The mother's status as a single parent can indirectly affect the care patterns given to children due to different load borne, lack of partner support, as well as economic conditions that will impact on the nutritional status of children. The purpose of the study was to see whether there were differences in the characteristics of the mother, child and family, differences in parenting, the level of nutritional adequacy, the frequency of child infections, and the nutritional status of the child from the mother as a single parent and not as a single parent. The research method uses a comparative study with a cross sectional approach with a purposive sampling technique. The total sample of 50 mothers as single parents and 50 mothers not as single parents. The normality test uses the Kolmogorov Smirnov test. Data analysis used independent sample test, Mann Whitney test, and Chi-square test for different tests, and Rank Spearman test for relationship test. The results showed different characteristics of mothers as single parents and not as single parents were occupational status and income per capita (p <0.05). Characteristics that did not differ were maternal age, education, number of family members, number of children, sex and age of the child (p <0.05). The different parenting patterns between the two groups were attitudes and practices (p <0.05) while knowledge did not differ (p≥0.05). The levels of nutritional adequacy that differed between the two groups were Energy Adequacy Level and Protein Adequacy Level (p <0.05). The nutritional status of children who differed between the two groups was the nutritional status based on the BB/U index (p <0.05) while based on the TB/U index and the BB/U did not differ (p≥0.05). Mother characteristics related to parenting are age, education, employment status and income per capita (p <0.05). There is a relationship between parenting and the level of nutritional adequacy and infection (p <0.05). There is a relationship between infection and nutritional adequacy level with the nutritional status of children (p <0.05).